Predominant T-cell epitopes of SARS-CoV-2 restricted by multiple prevalent HLA-B and HLA-C allotypes in Northeast Asia - Yu Zhao; Min Peng; Chengtao He; Min Li; Min Li; Xuelian Han; Xuelian Han; Qiang Fu; Yandan Wu; Fangping Yue; Chunguang Yan; Guangyu Zhao; et al. (Frontiers in Immunology)
Since the outbreak of novel coronavirus pneumonia (COVID-19), numerous T-cell epitopes in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteome have been reported. However, most of the identified CD8+ T-cell epitopes have been restricted primarily by HLA-A allotypes. The epitopes restricted by HLA-B and HLA-C allotypes are limited. This study focuses on the screening of T-cell epitopes restricted by 13 prevalent HLA-B and 13 prevalent HLA-C allotypes, which cover over 70% and 90% of the Chinese and Northeast Asian populations, respectively. Totally, 67 HLA-B restricted and 53 HLA-C restricted epitopes were validated as immunogenic epitopes with a herd predominance rate by peptide-PBMCs ex vivo coculture experiments using the PBMCs from convalescent Chinese cohort. In addition, 26 transfected cell lines expressing indicated HLA-B or HLA-C allotype were established, and used in the competitive peptide binding assays to define the affinities and cross-restriction of each validated epitope binding to HLA-B or HLA-C allotypes. These data will facilitate the design of T-cell-directed vaccines and SARS-CoV-2-specific T-cell detection tools tailored to the Northeast Asian population. The herd test of functionally validated T-cell epitopes, and the competitive peptide binding assay onto cell line array expressing prevalent HLA allotypes may serve as an additional criterion for selecting T-cell epitopes used in vaccine.